2008
DOI: 10.1007/s10551-008-9830-0
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor–Subordinate Guanxi and Employee Work Outcomes: The Mediating Role of Job Satisfaction

Abstract: supervisor–subordinate guanxi, job satisfaction, participatory management, turnover intentions, organizational commitment, China,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(158 citation statements)
references
References 52 publications
(58 reference statements)
8
149
1
Order By: Relevance
“…As a consequence, employees who have good guanxi with their supervisors tend to receive more bonuses and are more likely to be promoted (Law et al 2000). Empirical research also attests that close guanxi bonds between coworkers facilitate job related support and recognition for each other (Cheung et al 2009), and to social relations outside work (Law et al 2000). Guanxi emphasizes emotional attachment and obligations, thus, the more supervisors and employees develop a high-quality work relationship and interact with each other, the more likely it is that employees exhibit organizational citizenship behavior (Wong et al 2003), organizational commitment (Cheung et al 2009) and work engagement.…”
Section: Guanxi Exchange In the Jd-r Modelmentioning
confidence: 94%
See 1 more Smart Citation
“…As a consequence, employees who have good guanxi with their supervisors tend to receive more bonuses and are more likely to be promoted (Law et al 2000). Empirical research also attests that close guanxi bonds between coworkers facilitate job related support and recognition for each other (Cheung et al 2009), and to social relations outside work (Law et al 2000). Guanxi emphasizes emotional attachment and obligations, thus, the more supervisors and employees develop a high-quality work relationship and interact with each other, the more likely it is that employees exhibit organizational citizenship behavior (Wong et al 2003), organizational commitment (Cheung et al 2009) and work engagement.…”
Section: Guanxi Exchange In the Jd-r Modelmentioning
confidence: 94%
“…Empirical research also attests that close guanxi bonds between coworkers facilitate job related support and recognition for each other (Cheung et al 2009), and to social relations outside work (Law et al 2000). Guanxi emphasizes emotional attachment and obligations, thus, the more supervisors and employees develop a high-quality work relationship and interact with each other, the more likely it is that employees exhibit organizational citizenship behavior (Wong et al 2003), organizational commitment (Cheung et al 2009) and work engagement. However, guanxi reciprocity requires that the individual continuously invests and puts effort into relationships with others, which might exhaust their energy (Warren et al 2004).…”
Section: Guanxi Exchange In the Jd-r Modelmentioning
confidence: 99%
“…Huang (2008, 481) argues that 'state managers can engage in rent-seeking activities which advantage them personally, thereby creating room for guanxi influences in employment processes' . Cultural values are therefore pervasive in SOEs and guanxi may still be strong (Bedford, 2011;Cheung et al, 2009). Since the 1990s, SOEs have undergone transformation to enhance their competitiveness in the market economy.…”
Section: Guanxi and People Management In State-owned Enterprisesmentioning
confidence: 99%
“…Current Chinese research has paid limited attention to between guanxi/ job satisfaction relations. However, according to Cheung et al (2009), employees who maintain good guanxi with supervisors find it easier to meet job requirements. Further, while not limited to SOEs, Zhai, Lindorff, and Cooper (2013) have demonstrated that guanxi has a positive relationship with job satisfaction.…”
Section: Employee Attitudesmentioning
confidence: 99%
See 1 more Smart Citation